2008
DOI: 10.1038/sj.bjp.0707661
|View full text |Cite
|
Sign up to set email alerts
|

RIC‐3: a nicotinic acetylcholine receptor chaperone

Abstract: RIC-3 is a transmembrane protein which acts as a molecular chaperone of nicotinic acetylcholine receptors (nAChRs). For some nAChR subtypes (such as homomeric a7 neuronal nAChRs), RIC-3 is required for efficient receptor folding, assembly and functional expression. In contrast, for other nAChR subtypes (such as heteromeric a4b2 neuronal nAChRs) there have been reports that RIC-3 can both enhance and reduce levels of functional expression. There is also evidence that RIC-3 can modulate maturation of the closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 69 publications
2
136
0
1
Order By: Relevance
“…Expression studies using heterologous systems have shown that nAChR assembly is a tightly regulated and ordered process, which requires appropriate subunit-subunit interactions and perhaps other proteins (chaperones) that can assist receptor assembly [52,53]. Vertebrate nAChR subunits may co-assemble in many possible combinations, and many more subtypes have been heterologously expressed than those identified in vivo.…”
Section: Nachr Subtype Assemblymentioning
confidence: 99%
“…Expression studies using heterologous systems have shown that nAChR assembly is a tightly regulated and ordered process, which requires appropriate subunit-subunit interactions and perhaps other proteins (chaperones) that can assist receptor assembly [52,53]. Vertebrate nAChR subunits may co-assemble in many possible combinations, and many more subtypes have been heterologously expressed than those identified in vivo.…”
Section: Nachr Subtype Assemblymentioning
confidence: 99%
“…RIC-3 is thought to act as a chaperone promoting AChR folding, assembly, or maturation (reviewed in ref. 15). unc-74 was identified in early screens for resistance to levamisole (4).…”
mentioning
confidence: 99%
“…For example, RIC-3, a transmembrane protein which acts as a molecular chaperone, is required for efficient receptor folding, assembly, and functional expression of the α7 nAChR (Millar 2008). Similar chaperon proteins have not been described in the case of α9α10 receptors.…”
Section: Discussionmentioning
confidence: 99%